Book Reviews / Comptes rendus (Food & History, 2021)
Abstract Cookbooks, Hunger and Regionalism in Spanish Food History Maria Jose SEVILLA, Delicioso: A History of Food in Spain (London: Reaktion Books, 2019). Lara ANDERSON, Control and Resistance: Food and Discourse in Franco Spain (Toronto: University of Toronto Press, 2020). Maria Angeles PEREZ SAMPER, Comer y beber: Una Historia de la alimentación en España (Madrid: Catedra, 2019). Jillian Williams The Last “National Dish”? Food, Nationalism and Historiography Atsuko ICHIJO, Venetia JOHANNES, Ronald RANTA (eds), The Emergence of National Food: The Dynamics of Food and Nationalism (London: Bloomsbury, 2019). Michelle T. KING (ed.), Culinary Nationalism in Asia (London: Bloomsbury, 2019). Katarzyna J. CWIERTKA, Ewa MACHOTKA (eds), Consuming Life in Post-Bubble Japan: A Transdisciplinary Perspective (Amsterdam: Amsterdam University Press, 2018). Matthijs Kuipers Paul ERDKAMP, Claire HOLLERAN (eds), The Routledge Handbook of Diet and Nutrition in the Roman World (London/ New York: Routledge, 2019). Robin Nadeau IBN MUBĀRAK SHĀH, The Sultan’s Feast. A Fifteenth-Century Egyptian Cookbook. Edited, translation and introduction by Daniel L. NEWMAN (London: Saqi Books, 2020). Marianne Brisville Troy BICKHAM, Eating the Empire: Food and Society in Eighteenth-Century Britain (London: Reaktion Books, 2020). Jessica Mcintyre Joshua SPECHT, Red Meat Republic: A Hoof-to-Table History of How Beef Changed America (Princeton: Princeton University Press, 2019). Zachary Nowak Natacha CHEVALIER, Food in Wartime Britain: Testimonies from the Kitchen Front, 1939-1945 (London: Routledge, 2020). Bryce Evans